2003
DOI: 10.1021/jp036559d
|View full text |Cite
|
Sign up to set email alerts
|

Desorption of Acetone from Alkaline-Earth Exchanged Y Zeolite after Propane Selective Oxidation

Abstract: The desorption of products from a series of alkaline-earth exchanged Y zeolites after room-temperature propane selective oxidation was investigated by in situ infrared and mass spectroscopy. The intermediate product, isopropylhydroperoxide (IHP), did not desorb during temperature-programmed-desorption experiments but converted into acetone and water. Decomposition rate of IHP, produced from propane and oxygen at room temperature, into acetone increased in the order BaY < SrY < CaY ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…It has been discussed in our previous paper 11,14 that propane partial oxidation to acetone on alkaline-earth-exchanged Y zeolite proceeds via IHP as a reaction intermediate, which results in the overall reaction…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been discussed in our previous paper 11,14 that propane partial oxidation to acetone on alkaline-earth-exchanged Y zeolite proceeds via IHP as a reaction intermediate, which results in the overall reaction…”
Section: Resultsmentioning
confidence: 99%
“…11,14 It is not yet clear how many Ca 2+ ions in the supercage position are converted to Ca(OH) x species. This is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually an addition of excess initiator is needed to activate the free-radical chain reaction, but the reaction can be self-activated by mild thermal conditions due to the strong electrical field of the zeolite structure [1,17]. Researchers have demonstrated that alkali and alkaline earth exchanged zeolite Y selectively oxidizes alkanes at low temperature [1,6,8,19]. The reaction mechanism proposed by Frei and coworkers involved a charge-transfer complex RH + O 2 À [6].…”
Section: Catalytic Oxidation Of 1-butene and Butane Over Zeolitesmentioning
confidence: 97%
“…A c c e p t e d M a n u s c r i p t 4 activation of propane and O 2 , but unfortunately also for a strong adsorption of product molecules like acetone [24]. Closing the catalytic cycle at low temperature would be possible, if these electrostatic forces could be turned off, or at least reduced to a value where the adsorbed products can be released from the surface with minor thermal activation.…”
Section: Of 38mentioning
confidence: 98%